Credit Cycle and Capital Buffers in Central America, Panama, and the Dominican Republic - Flamini, Valentina (IMF Working Papers; Working Paper ;, 2019)
Credit is key to support healthy and sustainable economic growth but excess aggregate credit growth can signal the build-up of imbalances and lead to systemic financial crisis. Hence, monitoring the credit cycle is key to identifying vulnerabilities, particularly in emerging markets, which tend to be more exposed to sudden external shocks and reversal in capital flows. We estimate the credit cycle in Central America, Panama, and the Dominican Republic and find that the creadit gap is a powerful predictor of systemic vulnerability in the region. We simulate the activation of the Basel III countercyclical capital buffers and discuss the macroprudential policy implications of the results, arguing that countercyclical macroprudential policies based on the credit gap could prove useful to enhance the resilience of the region's financial sector but the activation of macroprudential instruments should also be informed by the development of other macrofinancial variables and by expert judgment.